Possible Ways of Positive Education – from a Hungarian Aspect - Ladnai, Attiláné (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This paper examines the emerging trends of humanistic and positive psychology: it points out a certain segment of this trend which benefi ts in the context of education. Seligman’s model: the individual level of psychological capital is introduced in details in connection with the author’s partial qualitative results from an ongoing research. In order to explore the similarities between the contents of Positive Education (as theoretical background) and Blue Bird (the examined good practice), this research focuses on extracting those indicators from the theoretical background, which serve as bases for the qualitative data analyzing methods such as in-depth interviews and the data reduction. A further direction of this research may be the comparison of the personal resource of psycho logical capital with the inclusive environment in education focusing on similarities and analogies. Keywords: black pedagogy, positive psychology, positive education/pedagogy, emotional intelligence, model of PERMA